Influence of fruit availability on macronutrient and energy intake by female chimpanzees. (14th June 2019) - Uwimbabazi, Moreen; Rothman, Jessica M.; Basuta, Gilbert I.; Machanda, Zarin P.; Conklin‐Brittain, Nancy L.; Wrangham, Richard W.
Abstract: Daily energy intake of adult female mammals is influenced by environmental conditions and physiological requirements, including reproduction. We examined the effects of fruit availability on macronutrient and metabolisable energy (ME) intake by adult female chimpanzees ( Pan troglodytes schweinfurthii ) of the Kanyawara community in Kibale National Park, Uganda, from January 2014 through June 2015. Drupe fruits were abundant for 4 months, whereas the other 14 months were dominated by fig fruits. The mean daily intake of food (dry matter) and ME did not differ between drupe‐months and fig‐months. However, foraging costs were higher during fig‐months, as indicated by a 20% increase in feeding time. Furthermore, during drupe‐months female chimpanzees ingested more water‐soluble carbohydrates and lipids, and less available protein and neutral detergent fibre. Although ME intake did not differ consistently between drupe‐months and fig‐months, they consumed more on days when ripe fruit dominated the diet than when leaves and pithy stems dominated the diet. Our data suggest that differences in diet quality between drupes and figs can have important effects on frugivore foraging and that they influence net energy gain more by their effects on macronutrient composition or foraging cost than by their direct impact on energy intake. Résumé: L'apport énergétique quotidien des mammifères femelles adultes est influencé par les conditions environnementales et les exigences physiologiques, y compris la reproduction. Nous avons examiné les effets de la disponibilité des fruits sur l'apport en macronutriments et en énergie métabolisable chez les chimpanzés femelles adultes (Pan troglodytes schweinfurthii) de la communauté de Kanyawara dans le parc national de Kibale en Ouganda de janvier 2014 à juin 2015. Les fruits de Drupe étaient abondants pendant quatre mois, tandis quatorze mois ont été dominés par les figues. L'apport quotidien moyen en nourriture (matière sèche) et en énergie métabolisable n'a pas différé entre les mois de drupe et les mois de figue. Cependant, les coûts de recherche de nourriture étaient plus élevés pendant les fig‐mois, comme l'indique une augmentation de 20% du temps d'alimentation. En outre, pendant les drupe‐mois, les femmes chimpanzés ont ingéré plus de glucides et de lipides hydrosolubles et moins de protéines et de fibres détergentes neutres. Bien que l'apport en énergie métabolisable n'ait pas différé de façon constante entre les mois de drupe et les mois de figue, ils en ont consommé davantage les jours où les fruits mûrs dominaient le régime que lorsque les feuilles et les tiges moelleuses dominaient le régime. Nos données suggèrent que les différences de qualité de l'alimentation entre drupes et figues peuvent avoir des effets importants sur la recherche de nourriture frugivore et qu'elles influencent davantage le gain d'énergie net par leurs effets sur la composition en macronutriments ou le coût de la recherche de nourriture que par leur impact direct sur l'apport énergétique.